Foreign Direct Investment of Chinese State-Owned Enterprise in Canada – A Continuation of Canada’s FDI Narratives - Goyer-Morley, Jerome (Université d'Ottawa | University of Ottawa, 2023)
This paper seeks to build on the work of Mattlin and Rajavuori (2023), who found that causal narratives played a key role in the shifting perceptions of foreign direct investment (FDI) from Chinese state-owned enterprises (SOEs). These shifting perceptions, in turn, led to a riskification of FDI from those firms. That is to say, FDI underwent a process similar to securitization, where the end goal is risk management rather than the total annihilation of the threat. This paper will attempt to use the same analytical framework to discover if FDI in Canada has undergone a similar riskification process, and, if so, if similar causal narratives are to blame. I find that, much like with the Nordic countries examined by Mattlin and Rajavuori, Canada has riskified FDI and changed how FDI controls are applied to Chinese SOEs due to the proliferation of causal narratives, rather than a change in the risk of FDI from said firms themselves, and that this riskification of FDI is a continuation of a much broader historical trend rather than an entirely new phenomenon.